SPLINE FINITE DIFFERENCE METHOD FOR A CLASS OF BOUNDARY-VALUE PROBLEMS - Khan, I.; Aziz, T.; Khan, A.; El-Sayed, S. M. (Journal of the Indonesian Mathematical Society, 2008)
"Pdf file"DOI :Â http://dx.doi.org/10.22342/jims.14.1.63.57-62